SPENT COFFEE GROUNDS BIO CHAR AS A LOW-COST ADSORBENT FOR METHYLENE BLUE REMOVAL FROM AQUEOUS SOLUTION: OPTIMISATION USING RESPONSE SURFACE METHODOLOGY - Mohamad, M. (Asian Research Publishing Network, 2020)
This research studied the application of Spent Coffee Ground Bio char (SCGB) for the removal of Methylene Blue (MB) from aqueous solution. The experiments were designed in two methods: classical and optimization by a combination of Response Surface Methodology (RSM) and Central Composite Design (CCD). Batch adsorption studies were carried out to investigate the influence of adsorption parameters, namely, adsorbent dosage, initial concentration and contact time on the response of MB removal () and adsorption capacity (mg/g). The interaction effects of the variables to the responses were studied using the three dimensional (3D) surface graph. The optimum conditions for MB removal () are adsorbent dosage of 0.2 g, contact time of 27.59 min, and initial concentration of 10.08 mg/L. The optimum conditions for adsorption capacity were found at adsorbent dosage of 0.1 g, contact time of 30 minutes and initial concentration of 30 mg/L. The determination coefficient (R2) of response surface quadratic model has proven significant at a confident level of 92 and 99 for MB removal and MB adsorption capacity, respectively. So, it was concluded that the SCGB can be used as a low-cost adsorbent for MB removal from aqueous solution. Â© (publication year), (publisher). All rights reserved.